(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
The advent of the Covid-19 pandemic implied challenging scenarios for scientists and political leaders, who found themselves grappling with an emergency that demanded quick decision-making and full of uncertainties. In this context, behavioral sciences played a role that was as relevant as it was controversial, since some decisions allegedly taken based on such sciences would come to be severely criticized by the scientific community itself. This text provides considerations on the role of behavioral sciences in the context of combating the pandemic, based on an examination of a sample of recent studies. The results are divided into four topics, which involve general guidelines from the scientific community for the formulation of interventions, the role of nudges as a form of behavioral intervention, the advantages and disadvantages of democratic and authoritarian political regimes in combating the crisis, and, finally , some misconceptions of effectively experienced public policies that were the subject of controversy.